Interfacial behavior between normal substrate and green ultra‐high‐performance fiber‐reinforced concrete under elevated temperatures - Abo Sabah, Saddam H.; Zainal, Nur L.; Muhamad Bunnori, Norazura; Megat Johari, Megat A.; Hassan, Mohd H. (Wiley, 2019)
This study assesses the effects of elevated temperatures (100, 200, 300, 400, and 500°C) on the bonding behavior of normal concrete (NC) substrate as old concrete and the new Green Universiti Sains Malaysia Reinforced Concrete (GUSMRC) as a repair material through slant shear, pull-off, splitting tensile, and flexural tests. Sandblasting (SB) and grinding (GR) surface treatments were employed to enhance the bond strength of the NC/GUSMRC composite. The research also evaluates the mechanical characteristics of the GUSMRC mix which 50% of its content is ultrafine palm oil fuel ash prior to and after the exposure to elevated temperatures. The results showed degradation in the mechanical properties of the monolithic GUSMRC and the bonding strength of the NC/GUSMRC composite after exposure to elevated temperatures; however, the bonding quality is excellent. Moreover, the SB surface treatment enhanced the interfacial bonding more than the GR surface treatment before and after elevated temperature exposure. © 2019 fib. International Federation for Structural Concrete